Quality of cataract-related videos on TikTok and its influencing factors: A cross-sectional study - Jiamin Cao; Feng Zhang; Ziyi Zhu; Wei Xiong (Digital Health)
Objective Short videos are increasingly being used to disseminate health information. However, the quality of videos on common ophthalmic conditions such as cataract has not been systematically evaluated. Methods This study employed a cross-sectional design. The TikTok platform was searched using the term “cataract” from 20:00 to 24:00 on 8 November 2024, without any restrictions. The top 100 retrieved videos were included in the study. They were rated using The Journal of American Medical Association ( JAMA ) benchmark criteria, Global Quality Score (GQS) scale, modified Decision-making Information Support Criteria for Evaluating the Reliability of Non-randomised Studies score, and Patient Education Materials Assessment Tool for Audio Visual Content. Videos by different groups were compared for quality and their underlying factors. Results The top 100 videos had an average of 2009.1 likes, 795.65 comments, 2628.91 shares, and 554.08 saves. Their JAMA benchmark criteria, GQS, the modified Decision-making Information Support Criteria for Evaluating the Reliability of Non-randomised Studies score, and the Patient Education Materials Assessment Tool for Audio Visual Content score ratings differed ( p  < .05) with account ownership, doctor rank, and video content. More videos were uploaded by institutions and physicians than by nonphysicians ( p  < .05). The number of likes, comments, favorites, and shares of videos was not correlated with quality (Spearman correlation; p  > .05). Further regression analysis confirmed that video quality can be predicted using account ownership. Conclusion The quality of cataract-related short videos on platforms has room for improvement. Users may estimate video quality based on the identity of the content creator.